Optimal charging coordination of electric vehicles in unbalanced electrical distribution system considering vehicle-to-grid technology - Sabillon, A. Carlos F. [UNESP]; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
A mixed integer linear programming (MILP) formulation is proposed in this paper to solve the problem of optimal charging coordination of electric vehicle (EVs) in unbalanced electrical distribution system (EDS) considering vehicle-to-grid (V2G) technology. The imbalance of the system circuits and loads has been taken into account. The developed method defines an optimal charging schedule for the EVs which considers the EVs arrival and departure times and their arrival state of charge; the energy contribution of EVs equipped with vehicle-to-grid technology and distributed generators are considered as well. The classical optimization techniques used to solve the MILP formulation guarantee the optimal solution of the problem. The model was written in the mathematical modeling language AMPL and solved using the commercial solver CPLEX. The presented formulation was tested in a 34-node distribution system and a comparison of the obtained charging schedule on scenarios with V2G and distributed generation was made.
Keywords: Charging Coordination Problem; Electric Vehicles; Mixed Integer Linear Programming; Vehicle-to-Grid